The Conspiracy of Silence: Cancer Patient Right to Know the Truth - Víctor Manuel Medina Pérez; Patricia Gil Pérez; Ahyní Abeledo Alfonso (Revista Finlay, 2017)
Health staff faces, in daily practice, the traditional polemic of telling the truth on an ecologic diagnosis. Familial mediation is one of the main causes of appealing to the so called conspiracy of silence due to several factors: ranging from emotional –affective up to psychogenetic ones. In this sense it is necessary for health professionals to respect the bio-ethic laws keeping a doctor-patient communication from empathy and understanding of patient’s individuals and their relatives.